Identification of Green Lane in its ability to absorb emissions on Main Arterial Street in Makassar City. Issue 1 (1st December 2022) - Harusi, N M R; Aly, S H; Mitani, Y; Junaid, M
Abstract: This study aims to know the number and variation of plant species and to analyze the potential for CO2 absorption from each type of plant in the green lane. The focused green lane is located on the main arterial road with length of 4.2 km, St. Urip Sumoharjo which is known as the longest and most congested road in Makassar City. This study was carried out by surveying and observation the tree species on the road and used image processing to validate the suspect of tree species through App. Meanwhile, the calculation of CO2 absorption is analyzed using the per plant species method by multiplying between the number of existing trees with the absorption capacity per plant species. As a result of the inventory, it was found that there were thirty-eight (38) tree species with a total of 2, 587 trees. The dominant tree species were Bougainvillea glabra with 693 trees (26.8%), and Tabebuia chrysantha with 339 trees (13.1%) located in the median side. With the total trees, it has the capacity to absorb CO2 of about 2, 478, 996 gr/hour. Additionally, Segment 5 and 6 have a highest CO2 absorption with 1, 278, 274 gr/hour and 786, 879 gr/hour respectively. It was caused by having the dominant typical plant species which are capable of absorbing the highest CO2 concentration, such as Bougainvillea glabra and Samanea saman at 1, 643.83 gr/hour.plant and 3, 252.1 gr/hour.plant.